2007
DOI: 10.1038/ni1441
|View full text |Cite
|
Sign up to set email alerts
|

Increased IgE-dependent mast cell activation and anaphylactic responses in mice lacking the calcium-activated nonselective cation channel TRPM4

Abstract: Mast cells are key effector cells in allergic reactions. Aggregation of the receptor FceRI in mast cells triggers the influx of calcium (Ca 2+ ) and the release of inflammatory mediators. Here we show that transient receptor potential TRPM4 proteins acted as calcium-activated nonselective cation channels and critically determined the driving force for Ca 2+ influx in mast cells. Trpm4 -/-bone marrow-derived mast cells had more Ca 2+ entry than did TRPM4 +/+ cells after FceRI stimulation. Consequently, Trpm4 -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
226
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(238 citation statements)
references
References 52 publications
10
226
2
Order By: Relevance
“…In mice lacking TRPM4, bone marrow-derived mast cells had augmented degranulation and released more histamine, leukotrienes and tumour necrosis factor due to increased Ca 2+ entry after FcepsilonRI stimulation (Vennekens et al, 2007). TRPM4 is also involved in the migration of bone marrow-derived mast cells by regulation of Ca 2+ -dependent actin cytoskeleton rearrangements (Vennekens et al, 2007;Shimizu et al, 2009). TRPM4 could be considered a therapeutic target in GI disorders that involve mast cell activation/degranulation, such as food allergies, mastocytosis and IBS (Bischoff, 2009).…”
Section: Trpm Channelsmentioning
confidence: 99%
“…In mice lacking TRPM4, bone marrow-derived mast cells had augmented degranulation and released more histamine, leukotrienes and tumour necrosis factor due to increased Ca 2+ entry after FcepsilonRI stimulation (Vennekens et al, 2007). TRPM4 is also involved in the migration of bone marrow-derived mast cells by regulation of Ca 2+ -dependent actin cytoskeleton rearrangements (Vennekens et al, 2007;Shimizu et al, 2009). TRPM4 could be considered a therapeutic target in GI disorders that involve mast cell activation/degranulation, such as food allergies, mastocytosis and IBS (Bischoff, 2009).…”
Section: Trpm Channelsmentioning
confidence: 99%
“…Bernd also demonstrated the role of TRPM5 in temperature-sensitivity of taste [8], and soon thereafter, he discovered the molecular mechanism of temperature sensing by TRP channels [12]. Bernd published the first phenotype of TRPM4, indicating a mast cell gain of function resulting in anaphylaxia and an increased type 1 allergic response [9]. He further discovered a wide range of pathological potential of TRPM4 in variety of diseases [6].…”
Section: Calcium Channelsmentioning
confidence: 99%
“…A second study used the same strategy to target a region of the gene spanning from exons 3 to 6 [67]. Studies using the TRPM4 deficient mice show that this channel, like TRPM2, plays a role in controlling intracellular calcium levels during mast cell activation and dendritic cell migration [66][67][68]. It has also been shown that this ion channel helps to limit catecholamine release from chromaffin cells, indicating that TRPM4 -/-mice have an increased sympathetic tone and hypertension [69].…”
Section: Trpm4mentioning
confidence: 99%
“…Knockout mice for TRPM4 were first generated by a Cre-loxP strategy that excised exons 15 and 16 of the gene (containing the first membrane-spanning segment of the protein), replacing them by a PGK-neo r cassette that was removed by Cre recombinase [66]. A second study used the same strategy to target a region of the gene spanning from exons 3 to 6 [67].…”
Section: Trpm4mentioning
confidence: 99%